COMMUNICATION SKILLS: A MANDATORY COMPETENCE FOR GROUND AND AIRPLANE CREW TO REDUCE TENSION IN EXTREME SITUATIONS DOI 10.5028/jatm.2010.02038110 - Ana Maria Vieira; Isabel Cristina dos Santos (Journal of Aerospace Technology and Management, 2011)
Communication skills have been considered a strategic asset for any kind of organization. However, technical-oriented enterprises usually emphasize the virtues of a cluster of technical competences and technological resources availability. So, this paper aimed to discuss communication skills development beyond technical communication in a high technology and technical-based operation, such as ground and flight operations. To do so, this article describes some tragic-ending cases in commercial aviation in which the poor quality of interpersonal communication was identified as the one of the most influential causes of the aircraft, or at least that was seen as a compelling force for creating the perfect backdrop for a disaster involving civilian aircrafts. Methodological procedures were basically addressed to a qualitative approach, supported by a documental research considering some of the most documented cases of aircraft accidents reported by the Aviation System Safety Report, issued by Federal Aviation Administration (FAA), USA, as well as reports of accidents provided by The National Transportation Safety Board (NTSB), USA, and by the Center for Aircraft Research and Prevention (Cenipa), Brasil.